How do you simplify #(x^9z^(-3))/(x^6z^2)#?

1 Answer
Mar 28, 2016

Answer:

# = x^ color(blue)(3 ) / z ^ color(blue)(5)#

Explanation:

#(x^9 z ^-3) / (x^6 z ^2#

# = (x^9 / x^6 ) * ( z ^-3 / z ^2)#

  • As per property:
    #color(blue)(a^m / a ^n = a ^(m-n)#

# = x^ color(blue)((9 - 6) ) * z ^ color(blue)((-3 - 2)#

# = x^ color(blue)(3 ) * z ^ color(blue)(-5)#

# = x^ color(blue)(3 ) z ^ color(blue)(-5)#

  • As per property:
    #color(blue)(1/a^-1 = a# , applying the same to #z#

# = x^ color(blue)(3 ) / z ^ color(blue)(5)#